Defect‐Engineered Co3O4@Nitrogen‐Deficient Graphitic Carbon Nitride as an Efficient Bifunctional Electrocatalyst for High‐Performance Metal‐Air Batteries. Issue 27 (3rd June 2022) - Tang, Wenhao; Teng, Kewei; Guo, Wengai; Gu, Fan; Li, Boya; Qi, Ruiyu; Liu, Ruiping; Lin, Yuyin; Wu, Miaomiao; Chen, Yihuang
Abstract: The ability to craft high‐efficiency and non‐precious bifunctional oxygen catalysts opens an enticing avenue for the real‐world implementation of metal‐air batteries (MABs). Herein, Co3 O4 encapsulated within nitrogen defect‐rich g‐C3 N4 (denoted Co3 O4 @ND‐CN) as a bifunctional oxygen catalyst for MABs is prepared by graphitizing the zeolitic imidazolate framework (ZIF)‐67@ND‐CN. Co3 O4 @ND‐CN possesses superb bifunctional catalytic performance, which facilitates the construction of high‐performance MABs. Concretely, the rechargeable zinc‐air battery based on Co3 O4 @ND‐CN shows a superior round‐trip efficiency of ≈60% with long‐term durability (over 340 cycles), exceeding the battery with the state‐of‐the‐art noble metals. The corresponding lithium‐oxygen battery using Co3 O4 @ND‐CN exhibits an excellent maximum discharge/charge capacity (9838.8/9657.6 mAh g −1 ), an impressive discharge/charge overpotential (1.14 V/0.18 V), and outstanding cycling stability. Such compelling electrocatalytic processes and device performances of Co3 O4 @ND‐CN originate from concurrent compositional (i.e., defect‐engineering) and structural (i.e., wrinkled morphology with abundant porosity) elaboration as well as the well‐defined synergy between Co3 O4 and ND‐CN, which produce an advantageous surface electronic environment corroborated by theoretical modeling. By extension, a rich diversity of other metal oxides@ND‐CN with adjustable defects, architecture, and enhanced activities may be rationally designed and crafted for both scientific research on catalytic properties and technological development in renewable energy conversion and storage systems. Abstract : A simple yet robust strategy is reported for high‐performance metal‐air batteries by utilizing metal oxides encapsulated within nitrogen‐deficient g‐C3 N4 (i.e., Co3 O4 @ND‐CN). The concurrent compositional (i.e., defect‐engineering), structural (i.e., wrinkled morphology with abundant porosity) elaboration, and the synergy between Co3 O4 and ND‐CN, produce an advantageous surface electronic environment corroborated by theoretical modeling, leading to compelling electrocatalytic processes and device performances.